Xiongnu-Xianbei layer in the Yakut Culture - Alexeev A.N.,; Bravina R.I. (Вестник археологии, антропологии и этнографии, 2022)
The aim of the article is to systematize and conceptualize the similarities between the paleo-ethnographic culture of the Yakuts and the Xiongnu of Central Asia, and to assess the possible ways of their appearance and incorporation into the new environment. In addition to the published data on this topic, the main source for the preparation of this paper was authors’ field archaeological material, collected during many years of expeditions. Among the materials of the Yakut Culture, a group of objects, the origin of which is associated with the Xiongnu-Xianbei time, includes some motifs of the traditional Yakut ornament, as well as artifacts — fragments of a compound bow, whistling arrowheads, Wushu coins, burial structures, etc. The earliest finds of these types of articles come from the cultural layers of the settlement of Ulakhan Segelennyah on the Olekma River, dated to the period within 110 BC — 350 cal AD. It is believed that the Xiongnu-Xianbei community was formed at the end of the 2nd — beginning of the 3rd c. AD after the fall of the Xiongnu Empire under the blows of warlike Mongol-speaking Xianbei. We conclude that in the Middle Ages the ancestors of the Yakuts had direct or indirect cultural ties with the Xiongnu. This could happen in the way of the resettlement of a small group of Xiongnu or Xiongnu-Xianbei to the north, or, more likely, it was the result of contacts between the Xiongnu or the ancestors of the Yakuts during their residence in the south of Siberia in the Early Middle Ages. The broadcasting of Xiongnu cultural traditions through the tribes of the Tashtyk Culture of the Minusinsk depression, with which, according to some researchers, the ancestors of the Yakuts once had active ethnic and cultural contacts, is also possible. In the Yakut Culture, the southern elements turned out to be in demand, as evidenced in particular by the funerary structures of the Yakuts in the Late Middle Ages. In the Lensky region, there was a further development of products of the indicated types, which led to the formation of a peculiar appearance of the traditional culture of the Yakuts.